Symbolic Capital of Kajang Tribe Black Clothing - Jepri Utomo; Syamsu Andi Kamaruddin; Arlin Adam; Andi Ihsan; Iwan Ramadhan (LPPM Universitas PGRI Sumatera Barat, 2024)
The Kajang tribal culture's usage of black attire shows a very symbolic depth. Wearing black attire enhances their sense of belonging and sets them apart from other groups as a symbol of strong cultural identity. Black attire honors humanity's bond with the universe and is a sign of cosmological views. Black clothes indicates the authority of traditional leaders and moral stature in daily life through ancestor traditions and adherence to customary law. Black clothing promotes community togetherness as a sign of equality. With a thorough comprehension of its significance, the Kajang tribal community promotes broad conservation efforts by raising awareness of the value of protecting the area's cultural history. To investigate the Kajang tribe's use of black traditional apparel, a qualitative ethnographic technique with a constructivist perspective was employed as the research method. The study's findings demonstrate that black apparel serves as more than just a piece of apparel it is a symbol of cultural identity, cosmological beliefs, ancestors' customs, adherence to customary law, and equality within the Kajang tribal society. According to the study's findings, the Kajang tribal community's social and cultural dynamics can be influenced by black clothing, which also has symbolic significance.